GR24, A Synthetic Strigolactone Analog, and Light Affect the Organization of Cortical Microtubules in Arabidopsis Hypocotyl Cells - Krasylenko, Yuliya; Komis, George; Hlynska, Sofiia; Vavrdová, Tereza; Ovečka, Miroslav; Pospíšil, Tomáš; Šamaj, Jozef (Frontiers in Plant Science, 2021)
Strigolactones are plant hormones regulating cytoskeleton-mediated developmental events in roots, such as lateral root formation, and elongation of root hairs and hypocotyls. The latter process was addressed herein by the exogenous application of a synthetic strigolactone, rac-GR24, and an inhibitor of strigolactone biosynthesis, TIS108, on hypocotyls of wild-type Arabidopsis and a strigolactone signalling mutant max2-1 (more axillary growth 2-1). Owing to the interdependence between light and strigolactone signalling, the present work was extended to seedling cultivation under a standard light/dark regime, or under continuous darkness. Given the essential role of the cortical microtubules in the cell elongation, their organization and dynamics were characterized under the conditions of altered strigolactone signalling using fluorescence microscopy methods with different spatiotemporal capacities, such as confocal laser scanning microscopy and structured illumination microscopy. It was found that GR24-dependent inhibition of hypocotyl elongation correlated with changes in cortical microtubule organization and dynamics, observed in living wild-type and max2-1 seedlings stably expressing genetically encoded fluorescent molecular markers for microtubules. Quantitative assessment of microscopic datasets revealed that chemical and/or genetic manipulation of strigolactone signalling affected microtubule remodelling, especially under light conditions. The application of GR24 in dark conditions partially alleviated cytoskeletal rearrangement, suggesting a new mechanistic connection between the cytoskeletal behaviour and the light-dependence of strigolactone signalling.